The role of free oxygen radicals in noise induced hearing loss - Karlidag, T; Yalçin, S; Öztürk, A; Üstündag, B; Gök, Ü; Kaygusuz, I; Susaman, N (Elsevier Sci Ltd, 2002)
The aim of this study was to investigate the role of cochlear damage caused by free oxygen radicals occuring as a result of exposure to noise and to determine the prophylactic effects of melatonin and methylprednisolone. Fifty male albino guinea pigs were randomly divided into five groups. All groups were exposed to 60 h of continuous wide band noise at 100 +/- 2 dB, except Group I. Group I was not exposed to noise or treated with drugs. Group II was exposed to noise and not treated with drugs. Group III was exposed to noise and treated with melatonin. Group IV was exposed to noise and treated with methylprednisolone. Group V was exposed to noise and treated with melatonin and methylprednisolone. A high dose of 40 mg/kg methylprednisolone and/or 20 mg/kg melatonin were administered intramuscularly 24 h before exposure to noise, immediately before noise exposure and once a day until noise exposure was completed. Just after the noise ended, guinea pigs were decapitated. Venous blood was obtained into tubes with EDTA and it was used to measure activity levels of plasma malondialdehyde, erythrocyte glutathione peroxidase and the cochlear tissue malondialdehyde. After the noise ended, in comparison group II with I; it was found that the malondialdehyde activity of the plasma and tissue had increased, the erythrocyte glutathione peroxidase activity levels had decreased and consequently, hearing thresholds had increased (P < 0.01). A significant difference was found in the malondialdehyde and erythrocyte glutathione peroxidase activity levels between groups II and III (P < 0.01) and the hearing thresholds exhibited a parallel trend (P < 0.05). The hearing threshold and malondialdehyde activity levels obtained from groups IV and V were found to be similar to those of group II (P > 0.05). As a conclusion, we suggest that the use of methlyprednisolone in order to prevent the cochlear damage caused by noise does not provide sufficient prophylaxy, however the use of melatonin provides a more effective prophylaxy, thus being a promising alternative. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: melatonin; methylprednisolone; cochlea; free oxygen radicals; noise induced hearing loss